INTEGRATION OF THE RISK-BASED APPROACH INTO PROJECT MANAGEMENT OF INTERNATIONAL INVESTMENT PROJECTS - Kapitanets, Svitlana; Kvasko, Alla; Zinoviev, Artur (Current Problems of Sustainable Development, 2026)
The relevance of the study is driven by the need to improve the efficiency of managing international investment projects amid military instability, globalisation, and digital transformation. Traditional approaches to risk management treat it as a supporting tool, which fails to address contemporary challenges. The aim of this article is to provide a theoretical substantiation and develop the conceptual foundations for integrating a risk-based approach into the management of international investment projects. Theoretical approaches to risk management are summarised, and specific risks of international investment projects (country, regulatory, currency, and sociocultural) are identified. A conceptual model for integrating the risk-based approach has been developed, covering strategic, tactical, operational, and feedback levels across all phases of the project lifecycle. The role of digital technologies (artificial intelligence, big data, cloud platforms) as an instrumental basis for implementing the approach is substantiated. Risk response mechanisms are proposed: financial hedging, political risk insurance (MIGA, ECA), contractual methods (EPC, BOT, public-private partnerships), and the creation of reserves with risk loadings. A five-level risk management maturity model for international investment projects has been developed. It has been established that integrating the risk-based approach reduces the required risk premium, increases the estimated net present value (NPV) of the project, and enhances the stability of cash flows. It is confirmed that applying strategic planning to risk management reduces the number of critical delays by 20%. Implementation barriers (cultural differences, data problems, conflicts of interest) are identified, and ways to overcome them are proposed. The limitations of the study relate to the lack of empirical verification on specific projects and the uniqueness of the Ukrainian military context. The risk-based approach should be viewed not as a supporting tool, but as a system-forming foundation for managing international investment projects. Its implementation contributes to increased investment attractiveness, stability, and adaptability of projects. Prospects for further research include empirical verification of the model, development of a methodology for assessing the return on investment (ROI) of risk management, and adaptation of the approach to different sectors of the economy.
Keywords: project management, risks, project management, foreign direct investment, international projects